Variability of chemical composition and antioxidant activity of essential oils between Myrtus communis var. Leucocarpa DC and var. Melanocarpa DC. (15th April 2016) - Petretto, Giacomo Luigi; Maldini, Mariateresa; Addis, Roberta; Chessa, Mario; Foddai, Marzia; Rourke, Jonathan P.; Pintore, Giorgio
Highlights: A chemical study on sixteen individual plants of M. communis L. was carried out. Differences in quali-quantitative content were observed between the samples. M. communis var. leucocarpa DC essential oil is characterized by myrtenil acetate. PCA proved to be a powerful tool to elaborate essential oils data. Abstract: Essential oils (EOs) from several individuals of Myrtus communis L. ( M. communis ) growing in different habitats in Sardinia have been studied. The analyses were focused on four groups of samples, namely cultivated and wild M. communis var. melanocarpa DC, characterized by red/purple berries, and cultivated and wild M. communis var. leucocarpa DC, characterized by white berries. Qualitative and quantitative analyses demonstrated different EO fingerprints among the studied samples: cultivated and wild leucocarpa variety differs mainly from the melanocarpa variety by a high amount of myrtenyl acetate (>200 mg/mL and 0.4 mg/mL in leucocarpa and melanocarpa varieties respectively). Conversely, the wild group is characterized by a higher amount, compared with the cultivated species, of linalool (about 110 mg/mL and 20 mg/mL respectively), linalyl acetate (about 24 mg/mL and about 6 mg/mL respectively) whereas EOs of the cultivated plants were rich in pinocarveol- cis compared with wild plants (about 2 mg/mL and about 0.5 mg/mL respectively). Principal component analysis applied to the chromatographic data confirm a differentiation and classification of EOs from the four groups of M. communis plants. Finally, antioxidant activity of the studied EOs shows differences between the various categories of samples.